2016
DOI: 10.26499/jentera.v5i1.351
|View full text |Cite
|
Sign up to set email alerts
|

Pantun Banjar sebagai Media Pendidikan Karakter

Abstract: AbstrakPantun Banjar adalah sastra lama yang lahir, tumbuh, dan berkembang di masyarakat Banjar. Pantun Banjar dapat memberikan sumbangan dalam pembentukan pola pikir, sikap, dan tingkah laku masyarakatnya. Hal itu berarti pantun Banjar dapat menjadi media pendidikan untuk membentuk karakter masyarakat Banjar itu sendiri. Metode penelitian yang digunakan adalah metode deskriptif. Dengan metode deskriptif nilai-nilai yang dapat membentuk karakter positif dalam pantun Banjar dapat diketahui, antara lain menjauhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 0 publications
1
4
0
5
Order By: Relevance
“…Thus, based on the above review, it can be concluded that regional rhymes, like Minangkabau rhymes, have the power as a medium for developing the Islamic character of students at various levels of Islamic education in Indonesia. This is in accordance with Yulianto's (2016) research on Banjar rhymes which can also contribute to the formation of the mindset, attitudes, and behavior of the community. Pantun Banjar can be an educational medium to shape the character of the Banjar community itself.…”
Section: E Hajjsupporting
confidence: 91%
“…Thus, based on the above review, it can be concluded that regional rhymes, like Minangkabau rhymes, have the power as a medium for developing the Islamic character of students at various levels of Islamic education in Indonesia. This is in accordance with Yulianto's (2016) research on Banjar rhymes which can also contribute to the formation of the mindset, attitudes, and behavior of the community. Pantun Banjar can be an educational medium to shape the character of the Banjar community itself.…”
Section: E Hajjsupporting
confidence: 91%
“…Pantun Banjar dapat memberikan sumbangan dalam pembentukan pola pikir, sikap, dan tingkah laku masyarakatnya. Hal itu berarti pantun Banjar dapat menjadi media pendidikan untuk membentuk karakter masyarakat Banjar itu sendiri (Yulianto, 2016). Suku atau masyarakat Banjar memiliki khazanah sastra daerah yang sangat beragam.…”
Section: Pendahuluanunclassified
“…Banyaknya khazanah sastra daerah Banjar ini menunjukkan tingkat kreativitas, inovasi, dan imajinasi yang sangat tinggi dari masyarakat pendukungnya. Tidak heran apabila sastra daerah Banjar ini Copyright © 2022, Pusat Publikasi S-1 Pendidikan IPS FKIP ULM mampu menjadi media pembentuk karakter dari masyarat pendukungnya tersebut (Yulianto, 2016).…”
Section: Pendahuluanunclassified
See 2 more Smart Citations